The EU Health Technology Assessment Regulation Halo Effect: Are Cross-Functional Teams Ready? - Sian Tanner; Rebecca Coady; Ana Lisica; Edel Falla; Anke van Engen (Journal of Market Access & Health Policy)
The focus of manufacturers preparing for implementation of the EU HTA Regulation (HTAR) in 2025 has understandably been on their market access teams, and how they can be best equipped to adapt to this significant change. Considering the critical nature of market access in ensuring innovation reaches patients, it should be no surprise that the EU HTAR will have impacts far beyond this function. Here, we utilize published EU HTAR guidance, a pragmatic literature review, internal analysis, and insights from engagements with manufacturers, to outline some of the key cross-functional considerations arising from JSC and JCA, and how manufacturers should account for these in their EU HTAR readiness plans.